Tatak Pilipino [episode no. 67]. ([Quezon City ABS-CBN, 1992)
A unique display of Pilipino ways and style.
Women affairs of Jose Rizal (5 min.) -- Beer house (10 min.) -- Cartoonist Whilce Portacio (5 min.) -- Sungka (10 min.) -- Mahjong (15 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Portacio, Whilce; Rizal, Jose; Games -- Philippines; Mah jong; Hotels, taverns, etc